I'm Lovin' It: How Fast Food Advertising Influences Meat-Eating Preferences. Issue 3 (4th March 2022) - Ellithorpe, Morgan E.; Zeldes, Geraldine; Hall, Elizabeth Dorrance; Chavez, Manuel; Takahashi, Bruno; Bleakley, Amy; Plasencia, Julie
Abstract : Overconsumption of red and processed meat is associated with a multitude of negative health outcomes. Previous research shows exposure to advertising messaging can influence dietary behaviors but research on the influence of meat advertising on diet, specifically, is scant. Theoretically informed by the Reasoned Action Approach, the present experiment randomly assigned participants to view a version of a print McDonald's advertisement that included meat imagery (a Big Mac), non-meat imagery (French fries), or no food (just the McDonalds' logo and slogan), which acted as a control. An online survey in the United States included 514 U.S. adults ( M age  = 51 years). Participants exposed to meat imagery compared to the non-meat imagery reported a higher desire to eat meat. The meat imagery and control conditions were also significantly associated with increased cognitive accessibility of meat concepts, compared to when respondents were shown the no-meat condition. Desire to eat meat, but not the cognitive accessibility of meat concepts, was significantly associated with attitude, normative pressure, and perceived behavioral control for avoiding eating meat one day per week; these constructs predicted intention and willingness to avoid meat. Results indicate that exposure to meat imagery in advertising does have the potential to influence meat consumption behavior and also has implications for the use of meat imagery in persuasive messaging for public health campaigns.